Clinical similarities between influenza A and B in children: a single-center study, 2017/18 season, Korea - Yu Na Oh; San Kim; Young Bae Choi; Sung Il Woo; Youn-Soo Hahn; Joon Kee Lee (BMC, 2019)
Abstract Background The global burden of seasonal influenza on medical care has been one of the greatest in the pediatric population. The attention drawn to influenza B was relatively low compared to influenza A, probably because the influenza B virus was thought to be less virulent and have a lower pandemic potential. This study aimed to compare the clinical features of influenza A and B in children. Methods This retrospective study included children diagnosed and treated for influenza as inpatients or outpatients during the 2017/18 influenza season at a tertiary referral hospital. Data regarding clinical characteristics, diagnoses, laboratory results, and vaccination histories were collected and reviewed. Results Over the study period, 128 patients with influenza A and 109 patients with influenza B were identified. The mean age of patients with influenza B was significantly higher than that of patients with influenza A (5.6 ± 4.4 vs 4.1 ± 4.4 years, p = 0.010). Fever was the most common manifestation of influenza followed by respiratory symptoms. No single symptom was specifically associated with either type of influenza. The total duration of fever (4.3 ± 2.3 vs 3.7 ± 2.6 days), 'time from fever onset to initiation of antivirals', and 'time from initiation of antivirals to defervescence' were similar between the two influenza types, even though all three time periods tended to be longer for influenza B. The platelet counts and proportions of neutrophils were higher for influenza A than for influenza B infections, although the values were within normal limits for both influenza types. Conclusions We found overall clinical similarities between influenza A and B with no less clinical significance or severity of influenza B compared to those of influenza A. Equal levels of awareness and attention should be paid to both influenza types.